Intracellular calcium stores drive slow non-ribbon vesicle release from rod photoreceptors - Chen, Minghui; Krizaj, David; Thoreson, Wallace B. (Frontiers in Cellular Neuroscience, 2014)
Rods are capable of greater slow release than cones contributing to overall slower release kinetics. Slow release in rods involves Ca2+-induced Ca2+ release (CICR). By impairing release from ribbons, we found that unlike cones where release occurs entirely at ribbon-style active zones, slow release from rods occurs mostly at ectopic, non-ribbon sites. To investigate the role of CICR in ribbon and non-ribbon release from rods, we used total internal reflection fluorescence microscopy (TIRFM) as a tool for visualizing terminals of isolated rods loaded with fluorescent Ca2+ indicator dyes and synaptic vesicles loaded with dextran-conjugated pH-sensitive rhodamine (pHrodo). We found that rather than simply facilitating release, activation of CICR by ryanodine triggered release directly in rods, independent of plasma membrane Ca2+ channel activation. Ryanodine-evoked release occurred mostly at non-ribbon sites and release evoked by sustained depolarization at non-ribbon sites was mostly due to CICR. Unlike release at ribbon-style active zones, non-ribbon release did not occur at fixed locations. Fluorescence recovery after photobleaching of endoplasmic reticulum (ER)-tracker dye in rod terminals showed that ER extends continuously from synapse to soma. Release of Ca2+ from terminal ER by lengthy depolarization did not significantly deplete Ca2+ from ER in the perikaryon. Collectively, these results indicate that CICR-triggered release at non-ribbon sites is a major mechanism for maintaining vesicle release from rods and that CICR in terminals may be sustained by diffusion of Ca2+ through ER from other parts of the cell.